2022
DOI: 10.1532/hsf.4297
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Procalcitonin and Interleukin-6 on Early Postoperative Pneumonia after Adult Cardiac Surgery: A Prospective Observational Study

Abstract: Background: Postoperative pneumonia (PP) is the most common primary infection after cardiac surgery, increasing the hospitalization expense and causing the consumption of healthcare resources. This study aimed to investigate the diagnostic value of procalcitonin (PCT) and interleukin-6 (IL-6) on early postoperative pneumonia after adult cardiac surgery. Methods: In this prospective observational study, patients with pneumonia and age- and sex-matched cases in our center from October 10, 2020 to January 31, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Therefore, we proposed whether multiple indicators could be combined to predict early sepsis and the prognosis of sepsis [17,18].Jerome et al [19] reported that PCT as a diagnostic test for infection/sepsis after major abdominal surgery had only moderate e cacy, limited sensitivity and speci city. Therefore, it is necessary to combine multiple in ammatory factors for analysis [20].Liang et al [21] retrospectively analyzed clinical data of 28 patients with bloodstream infections and sepsis admitted to ICU,and found that PCT, neutrophil to lymphocyte ratio (NLR), and APACHE II score were independent risk factors for patient death within 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we proposed whether multiple indicators could be combined to predict early sepsis and the prognosis of sepsis [17,18].Jerome et al [19] reported that PCT as a diagnostic test for infection/sepsis after major abdominal surgery had only moderate e cacy, limited sensitivity and speci city. Therefore, it is necessary to combine multiple in ammatory factors for analysis [20].Liang et al [21] retrospectively analyzed clinical data of 28 patients with bloodstream infections and sepsis admitted to ICU,and found that PCT, neutrophil to lymphocyte ratio (NLR), and APACHE II score were independent risk factors for patient death within 28 days.…”
Section: Discussionmentioning
confidence: 99%